Interest Groups as a Key Policy Actors: Representation and Influence in the United States Political System - Ambreen Aman; Zahid Yaseen (ASIAN Journal of International Peace & Security (AJIPS), 2025)
The interest groups, whose influence, representation, and overall impact on public opinion, are the main focus of the study, present a significant role in the public policymaking process in the United States. Through a qualitative case study method, the research investigates to what extent the interest groups are allowed to participate in the policy formation process by lobbying, advocacy, and public engagement. This study relies on a variety of data such as policy documents, congressional records, and lobbying disclosures, in addition to literature reviews. According to the study, one of the main reasons why interest groups are considered indispensable in the democratic governance process is that they articulate different societal interests, provide the policymakers with the necessary expertise, and serve as a mediator between the citizens and the government. Besides, the study also points out new access and influence problems that need to be tackled through further research.